Densities of Bornean orang‐utans (Pongo pygmaeus morio) in heavily degraded forest and oil palm plantations in Sabah, Borneo. Issue 8 (21st July 2019) - Seaman, Dave J.I.; Bernard, Henry; Ancrenaz, Marc; Coomes, David; Swinfield, Thomas; Milodowski, David T.; Humle, Tatyana; Struebig, Matthew J.
Abstract: The conversion of forest to agriculture continues to contribute to the loss and fragmentation of remaining orang‐utan habitat. There are still few published estimates of orang‐utan densities in these heavily modified agricultural areas to inform range‐wide population assessments and conservation strategies. In addition, little is known about what landscape features promote orang‐utan habitat use. Using indirect nest count methods, we implemented surveys and estimated population densities of the Northeast Bornean orang‐utan ( Pongo pygmaeus morio ) across the continuous logged forest and forest remnants in a recently salvage‐logged area and oil palm plantations in Sabah, Malaysian Borneo. We then assessed the influence of landscape features and forest structural metrics obtained from LiDAR data on estimates of orang‐utan density. Recent salvage logging appeared to have a little short‐term effect on orang‐utan density (2.35 ind/km 2 ), which remained similar to recovering logged forest nearby (2.32 ind/km 2 ). Orang‐utans were also present in remnant forest patches in oil palm plantations, but at significantly lower numbers (0.82 ind/km 2 ) than nearby logged forest and salvage‐logged areas. Densities were strongly influenced by variation in canopy height but were not associated with other potential covariates. Our findings suggest that orang‐utans currently exist, at least in the short‐term, within human‐modified landscapes, providing that remnant forest patches remain. We urge greater recognition of the role that these degraded habitats can have in supporting orang‐utan populations, and that future range‐wide analyses and conservation strategies better incorporate data from human‐modified landscapes. Abstract : Forest remnants in oil palm support orang‐utan populations, although at significantly lower densities than logged forest. Research Highlights: Forest remnants within oil palm estates can support substantial orang‐utan numbers, although at reduced density. Orang‐utan density is more influenced by forest structure than isolation from large forested areas in human‐modified landscapes of Borneo.